Design of Waste Management in Nuclear Medicine Isolation Room of Dr. Sardjito Central General Hospital - Efendi, Ahmad Mudzakir; Mondjo, Mondjo; Purwanti, Eli (Computational And Experimental Research In Materials And Renewable Energy, 2024)
The purpose of isolation room is to prevent radioactive contamination from the patient's metabolic processes. Because of that the radiation dose around the room and working area need to be limited. So that the value of the dose limits are not exceeded, the work area could be divided according to Perka Bapeten number 17 of 2012 Article 35. The working area can be divided into two parts: control region and supervision region. According to Perka Bapeten number 4 of 2013 Dose Limit Value (DLV) received in the control region has the potential to exceed 3/10 radiation workers DLV and the dose received in the supervision region has the potential of less than 3/10 radiation workers DLV and exceed people DLV. The isolation room is belong in the control region. The liquid waste from the isolation room is accommodated in the multi tank to delay it before being released to wastewater treatment plant. The isolation room needs ventilation using filters to prevent contamination via air circulation. The position of the preparation and radiopharmaceutical room and the waste storage room which is in the control region must be adjacent to the isolation room.Keywords: Isolation Room, Radioactive, Control Region, Supervision Region, DLV.